A membrane-associated form of sucrose synthase and its potential role in synthesis of cellulose and callose in plants. - Amor, Y (1995)
Sucrose synthase (SuSy; EC 2.4.1.13; sucrose + UDP reversible UDPglucose + fructose) has always been studied as a cytoplasmic enzyme in plant cells where it serves to degrade sucrose and provide carbon for respiration and synthesis of cell wall polysaccharides and starch. We report here that at least half of the total SuSy of developing cotton fibers (Gossypium hirsutum) is tightly associated with the plasma membrane. Therefore, this form of SuSy might serve to channel carbon directly from sucrose to cellulose and/or callose synthases in the plasma membrane. By using detached and permeabilized cotton fibers, we show that carbon from sucrose can be converted at high rates to both cellulose and callose. Synthesis of cellulose or callose is favored by addition of EGTA or calcium and cellobiose, respectively. These findings contrast with the traditional observation that when UDPglucose is used as substrate in vitro, callose is the major product synthesized. Immunolocalization studies show that SuSy can be localized at the fiber surface in patterns consistent with the deposition of cellulose or callose. Thus, these results support a model in which SuSy exists in a complex with the beta-glucan synthases and serves to channel carbon from sucrose to glucan.